AKTIVITAS LINGKUNGAN PESANTREN DALAM MEMBENTUK ADAB SOPAN SANTUN SANTRI PONDOK PESANTREN DARUSSALAM BLOKAGUNG - Masnida Masnida; Abidul Qomar (Jurnal At-Taujih, 2021)
The purpose of this study is to find out how the culture of Islamic boarding schools in building the character of students at Pondok Pesantren Darussalam Blokagung. In this study, researchers used qualitative research methods with 10 students as research subjects. Data was collected using observation, interviews, and documentation. The data were analyzed qualitatively by means of data collection, data reduction, data display, and drawing conclusions. The results of the study show that building the character of students in Islamic boarding schools must be through habituation, exemplary teachers/asatidz and all parties in Islamic boarding schools and parents at home. In carrying out learning in developing the character of students through the culture of Islamic boarding schools, using habituation and example in Islamic boarding schools as follows: 1) teaching honest actions, 2) teaching students about responsible attitudes, 3) teaching students about disciplinary actions, 4) working together with his friends, as well as spiritual activities in Pondok Pesantren Darussalam Blokagung.